Recurrent oral angioleiomyoma - V G Mahima; Karthikeya Patil; H S Srikanth (Contemporary Clinical Dentistry, 2011)
Angioleiomyomas are vascular variant of leiomyomas which are benign tumors of smooth muscle. They are exceedingly rare in the oral cavity. Malignant transformation of these tumors has also been reported occasionally which warrants knowledge of this soft tissue tumor. A 57 year old male patient reported with a 15 day history of an asymptomatic growth that had started insidiously in his lower left back tooth region. Clinical examination revealed a solitary, oval, sessile growth in the mandibular left retro molar region. Excisional biopsy was suggestive of Angioleiomyoma. A recurrence of the same was noted two months later which was also histopathologically reported as Angioleiomyoma. The same was confirmed using special stains. This case reports an unusual presentation of Angioleiomyoma with regards to both recurrence as well as rapid growth. It is important to be well aware of this uncommon entity as these tumors often can mimic or transform into malignancy. Precise clinicopathological examinations are therefore invaluable in establishing an accurate diagnosis and delivering suitable treatment.